The challenges faced by residents in affordable housing at Bayan Lepas, Pulau Pinang / Nur Hafizah Binti Aminudin and Norazmawati Md. Sani @ Abd. Rahim - Aminudin, Nur Hafizah; Md. Sani @ Abd. Rahim, Norazmawati (Universiti Teknologi MARA, Perak, 2023)
This study focuses on the challenges of Bayan Lepas residents in obtaining affordable housing in Bayan Lepas, Penang. Affordable housing is frequently characterized as suitable for low and medium incomes. However, Bayan Lepas, Penang's housing situation demonstrates that high-end housing is more expensive than inexpensive housing. As a result, Bayan Lepas locals struggle to possess their own homes. This study aims to determine the residents' challenges to obtaining affordable housing in Bayan Lepas, Pulau Pinang. Fifty heads of families from low- and middle-income groups in the Bayan Lepas area were chosen to fulfil the study's goals. Semi-structured interview techniques are used for data collection. The qualitative data is next subjected to thematic content analysis. This study identified six (6) challenges to obtaining affordable housing for the Bayan Lepas people. The high cost of living, the difficulty in getting bank loans, the high down payments, expensive homes, the low income, and the problem in qualifying for affordable housing are a few challenges. Hence, it is suggested that the local government take a more active role in raising the ability of Penang's citizens and the number of affordable homes on the island, particularly in the Bayan Lepas region.